Rancang Bangun Sistem Pemberian Pakan dan Minum Ayam Secara Otomatis - Margaretha Yohanna; Desy Tri Natasia Lumban Toruan (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
This result project built a system of feeding and drinking chicken automatically using ATMEGA-328 microcontroller. This automated tool uses two parts: the first container serves as a reservoir of food and water and the second container is functioned as a feed and water distribution place. The volume of feed and water is measured using ultrasonic sensor HC-SR04 which has a function to control the height of feed and water in reserve storage of feed and water. The microcontroller circuit as the controller receives input to know the volume of feed and water and send status data to GSM SIM900A module in the form of AT Command command to be forwarded to destination number then the result will be displayed in the form of message.